What is the standard form of y= (2x+14)(x+12)-(7x-7)^2y=(2x+14)(x+12)(7x7)2?

2 Answers

y = -47x^2+ 136x +119 y=47x2+136x+119

Explanation:

y = (2x+14)(x+12)-(7x-7)^2y=(2x+14)(x+12)(7x7)2

y=2x^2+24x+14x+168-(49x^2-98x+49)y=2x2+24x+14x+168(49x298x+49)

y=2x^2+24x+14x+168-49x^2+98x-49y=2x2+24x+14x+16849x2+98x49

y=-47x^2+136x+119y=47x2+136x+119

Aug 30, 2017

y=-47x^2+136x+119y=47x2+136x+119

Explanation:

The equation of a quadratic in standard form is: y=ax^2+bx+cy=ax2+bx+c

So, this question is asking us to find a, b , ca,b,c

y=(2x+14)(x+12) - (7x-7)^2y=(2x+14)(x+12)(7x7)2

It is probably simplier to break yy in its two parts first.

y = y_1 - y_2y=y1y2

Where: y_1 = (2x+14)(x+12)y1=(2x+14)(x+12) and y_2= (7x-7)^2y2=(7x7)2

Now, expand y_1y1

y_1 = 2x^2+24x+14x+168y1=2x2+24x+14x+168

= 2x^2+38x+168=2x2+38x+168

Now, expand y_2y2

y_2 = (7x-7)^2 = 7^2(x-1)^2y2=(7x7)2=72(x1)2

=49(x^2-2x+1)=49(x22x+1)

= 49x^2-98x+49=49x298x+49

We can now simply combine y_1 - y_2y1y2 to form yy

Thus, y= 2x^2+38x+168 -(49x^2-98x+49)y=2x2+38x+168(49x298x+49)

= 2x^2+38x+168 -49x^2+98x-49=2x2+38x+16849x2+98x49

Combine coefficients of like terms.

y = (2-49)x^2 + (38+98)x +(168-49)y=(249)x2+(38+98)x+(16849)

y= -47x^2 + 136x +119y=47x2+136x+119 (Is our quadratic in standard form)

a=-47, b=+136, c=+119a=47,b=+136,c=+119